Regionalizing Telecommunications Reform in West Africa - Kessides, Ioannis N.; Noll, Roger G.; Benjamin, Nancy C. (2012)
In recent years, there has been an increasing recognition that significant welfare gains could be realized through deep forms of regional integration which entail harmonization of legal, regulatory and institutional frameworks. Reforms that reduce cross-border transaction costs and improve the performance of backbone infrastructure services are arguably even more important for the creation of an open, unified regional economic space than trade policy reforms narrowly defined. This paper assesses the potential gains from regionalized telecommunications policy in West Africa. To this end, the paper: (i) discusses how regional cooperation can overcome national limits in technical expertise, enhance the capacity of nations credibly to commit to stable regulatory policy, and ultimately facilitate infrastructure investment in the region; (ii) identifies trade-distorting regulations that inhibit opportunities for regional trade and economic development, and so are good candidates for regional trade negotiations to reduce indirect trade barriers; and (iii) describes substantive elements of a harmonized regional regulatory policy that can deliver immediate performance benefits.